(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve student learning outcomes in science subjects through the application of the Picture and Picture learning model in Grade V at SDM Waimangura. The study used a Classroom Action Research (CAR) design with two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection techniques included observation of teacher and student activities, documentation, and learning outcome tests at the end of each cycle to measure improvements in student understanding. Data were analysed using quantitative descriptive analysis techniques by comparing learning completeness and average scores in each cycle. The results showed a significant improvement in student learning outcomes after the implementation of the Picture and Picture model. In cycle I, out of 22 students, 15 students (68%) did not achieve the minimum passing grade of 70. In cycle II, the number of students who achieved the minimum passing grade increased to 20 students (91%), while 2 students (9%) were still below the minimum passing grade. This improvement shows that the Picture and Picture model is effective in helping students understand ecosystem material and improve overall learning outcomes. Thus, this learning model is suitable for use as an alternative science learning strategy at Waimangura Secondary School